Cult cinema : an introduction - Mathijs, Ernest; Sexton, Jamie (Malden, MA : Wiley-Blackwell, 2011)
Cult Cinema: an Introduction presents the first in-depth academic examination of all aspects of the field of cult cinema, including audiences, genres, and theoretical perspectives. Represents the first exhaustive introduction to cult cinemaOffers a scholarly treatment of a hotly contested topic at the center of current academic debateCovers audience reactions, aesthetics, genres, theories of cult cinema, as well as historical insights into the topic.
Midnight Movies and SatanismContemporary Performances of Religious Cultism; Conclusion; Part II: Themes and Genres; Chapter 13: Exploitation and B Movies; B Movies and Classical Exploitation; Teenpics and Youth Culture; Nasty Trash: Exploitation in the 1970s; Exploitation in the Video Era; Conclusion; Chapter 14: Underground and Avant-garde Cinema; Cult and the Avant-garde of the 1920s; The American Underground of the 1950s and 1960s; Underground Goes Overground: The Midnight Movie; The Underground Today; Chapter 15: Cult Cinema and Drugs; Cult Movies and Drug Depiction.
Counterculture, Drugs and the "Head" Film.
Print version record.
Keywords: Cult films -- History and criticism; Cult films; Sensationalism in motion pictures; Fine Arts; Cult films; Electronic books; Criticism, interpretation, etc